Contratos de aliança e formas híbridas de contratos de construção - Pithon, Bruno Matos (2016)
This work analyzes the system of contracts related to the construction activity, on a hiring free environment and taking into consideration the creation of non-standard models and, therefore, hybrid. A range of subsidies for such is necessary: application of economic arguments; capacity of objectively operationalize the demands coming from such modalities of contracts, which always seeks to maximize results; need for speed and time savings in the constructions. It must be highlighted that such contract models are hybrids, but no illegal, since under Brazilian law prevails the principle of freedom of contract, as long as the basic requirements established by law are fulfilled, which are, lawful object, agents capable and compliance with the prescribed manner or no defense in law. In that contract free environment, have emerged types of construction contracts that vary from each othe r in different aspects, highlighting among them the risk allocation, yield and application of penalties, which directly impacts the form, content and value of the budget to be presented. Thus, it is necessary that the economic rationale prevails in contracting of large infrastructure projects, but also in other projects, generating a culture of participation among contractors, in order to provide faster constructions and at a lower cost, which would be of fundamental importance for the development of the country.